DECISION TO BECOME A STUDENT AT ISLAMIC FASHION INSTITUTE BANDUNG CITY THROUGH INSTAGRAM ADVERTISING (Case Study of Instagram Advertising Content @islamicfashioninstitute on Active Students of Islamic Fashion Institute): KEPUTUSAN MENJADI SISWA DI ISLAMIC FASHION INSTITUTE KOTA BANDUNG MELALUI ADVERTISING INSTAGRAM (Studi Kasus Konten Advertising Instagram @islamicfashioninstitute pada Siswa Aktif Islamic Fashion Institute) - Azzahra Fiesa Kanaya; Engkus Kuswarno; Centurion Chandratama Priyatna (SOSIOEDUKASI, 2025)
Islamic Fashion Institute (IFI) is a Course and Training Institution that focuses on Muslim fashion design. IFI utilizes Instagram advertising by creating content to attract people to become IFI’s students. However, IFI has active students with the majority from outside Bandung even though IFI itself is located in Bandung. The purpose of this study was to determine how the Islamic Fashion Institute's strategy uses Instagram advertising to market programs in its institution, to determine the factors that influence how Instagram advertising can influence students' decisions to enroll in IFI, and to determine the reasons why the majority of IFI students come from outside Bandung. This study uses a qualitative method with a case study approach. Data collection techniques are observation, interviews, and document studies. The informants in this study were the IFI’s management team, IFI’s active students, IFI’s alumni, and parents of students and IFI’s alumni. The data validity test in this study was source triangulation from the IFI General Manager and the Bandung City Education Office. The results of this study are that the majority of active IFI students who come from outside Bandung know IFI from Instagram advertising while IFI students who come from Bandung know IFI through word-of-mouth.